Are Urban-Rural Welfare Differences Growing in India? - Mehtabul Azam (Institute of Labor Economics (IZA), 2017)
Using data from the large scale consumption expenditure surveys collected by Indian National Sample Survey Organization, we examine the urban-rural welfare gap in India in 1983, 1993-94, 2004-05, and 2011-12 across the entire distribution. Our main measure of welfare is spatially adjusted per capita consumption expenditure. We find that the urban-rural gap increased considerably between 1993-94 and 2004-05, and increase is larger at the higher quantiles. Using the unconditional quantile regression decomposition, we find that majority of the gap is explained by the urban advantage in endowments in all four years. The contribution of the unexplained effect (differences in rewards) in urban advantage was negative in 1983 and 1993-94 across the entire distribution. We find that difference in educational distribution across urban and rural areas is the most important driver of the observed gap. We find similar patterns using income data for 2004-05 and 2011-12 from India Human Development Surveys.
Keywords: I32; 330; urban-rural welfare gap; unconditional quantile regression; India